2010
DOI: 10.1016/j.bone.2009.06.029
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of serotonin (5-hydroxytryptamine) in the skeleton and its mediation of the skeletal effects of low-density lipoprotein receptor-related protein 5 (LRP5)

Abstract: Novel molecular pathways obligatory for bone health are being rapidly identified. One pathway recently revealed involves gut-derived 5-hydroxytryptamine (5-HT) mediation of the complete skeletal effects of low-density lipoprotein receptor-related protein 5 (LRP5). Mounting evidence supports 5-HT as an important regulatory compound in bone with previous evidence demonstrating that bone cells possess functional pathways for responding to 5-HT. In addition, there is growing evidence that potentiation of 5-HT sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 54 publications
(122 reference statements)
3
69
0
1
Order By: Relevance
“…Pharmacological inhibition of gut-derived serotonin promotes bone formation and prevents bone loss in OVX mice (62,63). If confirmed, these findings may possibly provide a novel therapeutic approach in osteoporosis therapy, in addition to target LRP5/6 in osteoblasts for promoting bone formation in osteopenic disorders (64).…”
Section: Therapies In Pipelinementioning
confidence: 71%
“…Pharmacological inhibition of gut-derived serotonin promotes bone formation and prevents bone loss in OVX mice (62,63). If confirmed, these findings may possibly provide a novel therapeutic approach in osteoporosis therapy, in addition to target LRP5/6 in osteoblasts for promoting bone formation in osteopenic disorders (64).…”
Section: Therapies In Pipelinementioning
confidence: 71%
“…The functional impact of 5-HT signaling in the skeleton is still very much debated because both enhancing and inhibitory effects on bone formation have been depicted in response to serotonin (1). Such diverse effects may be explained by the concurrent expression of several 5-HT receptor subtypes (4, 6, 10, 11) and downstream couplings, which may vary according to the differentiation state of bone-forming cells.…”
Section: Discussionmentioning
confidence: 99%
“…Proper skeletal development and bone homeostasis notably necessitate a tight regulation of mineralization. Over the past few years, growing attention has been paid to the involvement of serotonin (5-hydroxytryptamine, 5-HT) 2 in bone biology (1). Indeed, beyond its role as a neurotransmitter in brain (2), platelet-stored 5-HT broadly participates to the homeostasis of various tissues.…”
mentioning
confidence: 99%
“…In vitro studies showed that mice with a null mutation in the 5‐HTT gene or mice treated with SSRIs exhibit reduced BMD, altered skeletal architecture, and reduced bone mechanical properties (Bliziotes 2010; Warden et al. 2010). …”
Section: Introductionmentioning
confidence: 99%